Cytokines impact natural killer cell phenotype and functionality against glioblastoma in vitro - Sivonen, Minna; Sirviö, Katja A.; Wojciechowski, Sara; Kailaanmäki, Anssi; Kaipainen, Satu; Bailey, Aubrey; Villalba, Martin; Kekarainen, Tuija (Frontiers in Immunology, 2023)
Natural killer (NK) cells are a part of the innate immune system and first-line defense against cancer. Since they possess natural mechanisms to recognize and kill tumor cells, NK cells are considered as a potential option for an off-the-shelf allogeneic cell-based immunotherapy. Here, our objective was to identify the optimal cytokine-based, feeder-free, activation and expansion protocol for cytotoxic NK cells against glioblastoma in vitro. NK cells were enriched from human peripheral blood and expanded for 16 days with different activation and cytokine combinations. The expansion conditions were evaluated based on NK cell viability, functionality, expansion rate and purity. The cytotoxicity and degranulation of the expanded NK cells were measured in vitro from co-cultures with the glioma cell lines U-87-MG, U-87-MG EGFR-vIII, LN-229, U-118 and DK-MG. The best expansion protocols were selected from ultimately 39 different conditions: three magnetic cell-selection steps (Depletion of CD3+ cells, enrichment of CD56+ cells, and depletion of CD3+ cells followed by enrichment of CD56+ cells); four activation protocols (continuous, pre-activation, re-activation, and boost); and four cytokine combinations (IL-2/15, IL-21/15, IL-27/18/15 and IL-12/18/15). According to our findings the ex-vivo proliferation capacity and functionality of NK cells is affected by multiple factors, such as the donor, composition of starting material, cytokine combination and the activation protocol. The cytokines modified the NK cells' phenotype and functionality, which was evident in their reactivity against the glioma cell lines. The expansion rates varied between 2-50-fold, depending on the donor and the expansion conditions. The best expansion rate and purity were gained with sequential selection (Depletion of CD3+ cells and enrichment of CD56+ cells) from the starting material and pre-activation with IL-12/18/15 cytokines, which are known to produce cytokine-induced memory-like NK cells. The cytotoxicity of these memory-like NK cells was enhanced with re-activation, diminishing the donor variation. The most cytotoxic NK cells were produced when cells were boosted at the end of the expansion with IL-12/18/15 or IL-21/15. To our knowledge,this is the first comprehensive comparative study performed to this extent, and these findings could be used for upscaling clinical NK cell manufacturing.